Demographic responses of North Atlantic seabirds to seasonal ocean warming - Kate Layton-Matthews; Charlotte E. Regan; Manuel Ballesteros; Kevin Hodges; Sebastien Descamps; Tycho Anker-Nilssen; Sigurd Benjaminsen; Francis Daunt; Robert T. Barrett; Lila Buckingham; Vegard Sandøy Bråthen; Signe Christensen-Dalsgaard; et al. (Proceedings of the National Academy of Sciences, 2025)
Climate-driven ocean warming is profoundly reshaping marine ecosystems, with cascading effects on biodiversity and trophic interactions. For migratory marine predators such as seabirds, demographic responses to warming depend on when and where populations are exposed across the annual cycle. Therefore, integrating demographic monitoring and tracking data, across broad geographic and temporal scales, is essential, given the spatial and seasonal variability in ocean warming. Here, we integrated long-term demographic data, seasonal distributions, and sea surface temperatures (SSTs) for 26 populations of five seabird species breeding in the North–East Atlantic to assess the effects of SSTs on reproduction, survival, and population growth trajectories. Demographic responses varied widely among populations and seasons, but negative effects were most consistently associated with warming during the autumn period postbreeding, particularly in the Barents and East Greenland Seas. Winter warming also corresponded to reduced survival, while breeding-season SSTs showed fewer significant effects on reproductive rates. Populations with dual responses to warming in both the breeding and nonbreeding seasons had the lowest projected population growth rates under future SSTs given a high emissions scenario. These results demonstrate that population vulnerability reflects the interaction between seabirds’ year-round distributions and regional ocean warming. This underlines the need to integrate year-round tracking and long-term monitoring to inform conservation strategies and marine spatial planning to ensure climate-resilient marine ecosystems.